How to Personalise Students Learning: Learning Guides and Follow-up Appointments - Llovet Díaz, Oihana; Fernández Saiz, Javier (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
Personalizing learning enables 21st-century learners to find personal meaning and value in what they learn. in this paper we will introduce two learning enablers that support personalization: 1-learning guides and 2- follow-up appointments. the systematization both in the design of learning guides and in their use by students, allows teachers to dedicate time to accompany the learning process of each student through follow-up appointments on a daily basis. such as the notion of human freedom, its types, its main features and meaning and its connection to values.